Pengaruh Pengembangan Kompetensi Terhadap Kepuasan Kerja dan Komitmen Organisasional dalam Meningkatkan Kinerja Karyawan Pada CV. Innovation Sciense Solution di Kota Samarinda - Zalfanda Helza, Zenobia; Soedarsono, Arybowo; Pusriadi, Tommy (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effect of competency development on job satisfaction and organizational commitment in improving employee performance at CV. Innovation Science Solution, Samarinda. Using a quantitative explanatory approach, data were collected from 43 employees and analyzed with SEM-PLS. The results show that competency development significantly influences job satisfaction, organizational commitment, and employee performance, both directly and indirectly through mediating variables. The findings imply that organizations should enhance competency development programs to improve satisfaction, strengthen commitment, and ultimately achieve better employee performance. Keywords: Competency Development, Job Satisfaction, Organizational Commitment, Employee Performance, SEM-PLS, Human Resource Management, Mediation Effect